Buckling behaviour of dual-thickness dished shells under uniform pressure - Surya Mani Tripathi; R. Muthukumar; S Anup (Forces in Mechanics, 2023)
The dual thickness dished shells are made of conical frustum with a closed stiff top at the smaller diameter end of the frustum. The dished shells are categorized as dual-thickness because of higher thickness of the top circular region than that of the conical region. The higher thickness of top flat circular portion makes this more stiffer. The buckling behaviour of these shells is similar to that of arches, spherical caps and shallow conical frustums. The variation in curvature of these shells and different stiffnesses of the conical and top circular region makes them very interesting and innovative. Making the top circular region stiffer avoids the need for stiff support in the top circular region for practical applications under uniform pressure. In the present study, a nonlinear finite element analysis on metallic dished shells of dual-thickness is attempted by varying different geometrical parameters such as thickness of conical region, height and top flat region radius of the shell under uniform pressure. This parametric analysis is carried out to find out the effect of elastic and elastic-perfectly-plastic material properties, boundary conditions and imperfection sensitivity of Eigen-mode type axisymmetric imperfections on the critical buckling pressure. It is found that material plasticity has a significant effect on the critical buckling pressure of dual-thickness dished shells. The effect of the axisymmetric Eigen-mode imperfections on critical buckling pressure is significant for the elastic material model and very small with elastic-perfectly-plastic material models. The information collected from the current study can be used for the detailed design of dual thickness dished shells.